GOOD CORPORATE GOVERNANCE, CONSERVATISME ACCOUNTING, REAL EARNINGS MANAGEMENT AND INFORMATION ASYMMETRY ON SHARE RETURN (Case Study on Manufacturing Companies Listed BEI 2013-2015) - Sugiyanto, Sugiyanto (Universitas Pakuan, 2018)
This study aims to analyze the influence of accounting conservatism, real earningsmanagement, and information asymmetry on stock returns. This study uses the sample of allmanufacturing companies listed on the Indonesia Stock Exchange during the period 2013 to 2015.The total number of companies used as sample research is 44 companies with observations for 3years. Pursuant to purposive sampling method, total of research sample is 132 financial report andannual report. The results of this study indicate: (1) Good corporate governance has a significantnegative effect on stock return with a significance value of 0.002 <0.050. (1) Conservatism with accrual-based conservatism proxy has a significant negative effect on stock return with asignificance value of 0.032 <0.050. (2) real earnings management with the proxy of discretionarycash flow has no effect on stock return with a significance value of 0.050. (3) informationasymmetry with proxy of bid-ask spread has no effect on stock return with significance value of0.453> 0.05.Keywords: Good Corporate Governance, Conservatism, Real Earnings Management, InformationAsymmetry, Stock Return.